Effect of nitrogen fertilizer placement on nitrogen uptake and yield of sweet corn (Zea mays L. saccharata) : a thesis presented in partial fulfilment of the requirements for the degree of Master of Agricultural Science in Plant Science at Massey University, New Zealand - Wongpichet, Kitti (Massey University, 1986)
Five placements of nitrogen fertilizer applied to sweet corn (Zea mays L. saccharata) at the four fully expanded leaf stage, that is control (no nitrogen), a band of nitrogen placed on the soil surface near the row, on the soil surface between the rows, at 3 cm depth between the rows and at 10 cm depth between the rows were studied following three sowing times. Total plant nitrogen and sap nitrate were determined along with total plant dry weight at six growth stages. Leaf extension and leaf appearance were also followed in order to monitor the response of plants to nitrogen fertilizer applied. Nitrogen fertilizer application resulted in significantly higher nitrogen uptake, plant dry weight and marketable ears under both dry and wet conditions. Nitrogen fertilizer applied at 10 cm depth between rows resulted in significantly higher nitrogen uptake, plant dry weight and marketable ears than that applied on the soil surface between rows under dry condition. Nitrogen fertilizer applied on the soil surface near the plants performed well under both dry and wet conditions. The sap nitrate test was more sensitive than total nitrogen measurement in indicating the timing of nitrogen uptake. Sap nitrate levels were influenced by nitrogen fertilizer application and soil water content. The general critical value of sap nitrate over the vegetative growing period was about 1000 ppm. The sap nitrate test appeared to be a very useful monitoring tool for plant nitrogen status. Further studies in the uses of sap nitrate test, especially the critical value, are needed. Use of leaf extension to detect the response of plants to nitrogen fertilizer applied was not successful. Nitrogen fertilizer application tended to accelerate leaf appearance under the low soil nitrogen status.
Keywords: Sweet corn; Fertilizers; Nitrogen fertilizers; Metabolism; Nitrogen